MINERAL PARAGENESIS OF THE SAPPHIRINE-BEARING ROCK FROM THE AUSTKAMPANE AREA OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イシズカ, ヒデオ; スズキ, サトコ; コジマ, ヒデヤス; ISHIZUKA, Hideo; SUZUKI, Satoko; KOJIMA, Hideyasu (National Institute of Polar Research, 1995)
P(論文) A sapphirine-bearing rock occurs in the Austkampane area of the Sør Rondane Mountains, East Antarctica, where sillimanite-garnet-biotite gneisses of the granulite facies are widespread. The constituent minerals of the rock include sapphirine, phlogopite, hydrous cordierite, plagioclase, gedrite, orthopyroxene, spinel, corundum, rutile and ilmenite. The bulk rock analyses show basaltic compositions in a broad sense, but in a strict sense they are enriched in Al_2O_3,MgO, Cr and Ni, suggesting a precursor with troctolitic composition. Among the constituent minerals, it is most characteristic that the sapphirine is never in direct contact with orthopyroxene, and between the two phases occur the hydrous cordierite-spinel symplectite. This indicates that the reaction sapphirine+orthopyroxene+H_2O=hydrous cordierite+spinel may have occurred. In the system MgO-Al_2O_3-SiO_2-H_2O, this reaction is pressure sensitive with a very shallow and negative dP/dT slope at about 4kbar on the P-T diagram. Geothermometers, including sapphirine-spinel, cordierite-spinel, and Al_2O_3 content at the Ml-site of orthopyroxene, yield around 820-870℃ for the assemblage prior to the reaction, and about 770℃ for the assemblage after the reaction. It follows that the sapphirine-bearing rock may have suffered nearly isothermal decompression after its peak metamorphism. Such a decompression has recently been reported from other terrains of East Antarctica, suggesting the geological episode common in these terrains. departmental bulletin paper